Peningkatan kapasitas pelaku UMKM melalui bimbingan teknis perpajakan di Desa Empus, Kecamatan Bahorok, Kabupaten Langkat - Aginta, Windy; Pasaribu, Aria Masdiana; Safriandi, Ferry (LPPM Universitas Al-Azhar medan, 2025)
This community service was conducted to provide technical guidance on taxation to MSME players in Empus Village, Bahorok District, Langkat Regency. The method is done by providing technical guidance. The results of this community service activity show that before the socialization was conducted, only about 20% of the community had knowledge of taxation techniques, while after the socialization, those who had knowledge of taxation techniques were 80%. Most of the participants have understood and are able to apply taxation techniques properly. This activity went smoothly and received a very positive response from the participants, who enthusiastically participated in the event from the beginning to the end and actively discussed the problems related to taxation calculation for MSME actors in Empus Village, Bahorok District, Langkat Regency.